Mental health symptoms and disorders in elite athletes: a systematic review on cultural influencers and barriers to athletes seeking treatment - Castaldelli-Maia, J. M.; Guilherme de Mello e Gallinaro, J.; Scialfa Falcão, R.; Gouttebarge, V.; Hitchcock, M. E.; Hainline, B.; Reardon, C. L.; Stull, T. (British Journal of Sports Medicine, 2019)
Objective: To summarise the literature on the barriers to athletes seeking mental health treatment and cultural influencers of mental health in elite athletes.